Earth Publishing Company records - Earth Publishing Company
Correspondence, business records, production materials, and other material relating to the publication of Earth, a leftist journal of literature and the arts founded and edited by Joseph Niver and published in Wheaton, Ill., and Salem, Ore., between April 1930 and July 1932. Includes correspondence with Jack Conroy, James T. Farrell, Romain Rolland, Upton Sinclair, and Frank Townshend.
Collection material in English.
Keywords: Conroy, Jack, -- 1898-1990 -- Correspondence; Farrell, James T. -- 1904-1979 -- Correspondence; Niver, Joseph; Rolland, Romain, -- 1866-1944 -- Correspondence; Sinclair, Upton, -- 1878-1968 -- Correspondence; Townshend, Frank, -- 1887- -- Correspondence; Earth (Salem, Or.); Earth (Wheaton, Ill.); American periodicals; Arts; Literature